Research of the Decorative Advantages of Coniferous Trees and Shrubs for Landscaping - Alexandra V. Semenyutina (Polish Society of Ecological Engineering (PTIE), 2022)
In the arid conditions of chestnut soils of the Volgograd region, natural populations of coniferous trees are practically absent, and Juniperus sabina is present from coniferous shrubs. The introduction of new species of coniferous plants can increase the biodiversity of the flora of the region. The participation of new coniferous species in the greening of settlements can contribute to the formation of comfortable and healthy living conditions for the population. The objects of the study were Juniperus virginiana L., J. sabina L., J. communis L., Thuja occidentalis L., Platycladus orientalis (L.) Franco, Pseudotsuga menziesii var. viridis (Schwer.) Franco, P. menziesii var. glauca (Mayr) Franco, growing in the nurseries of the Federal Research Center of Agroecology of the Russian Academy of Sciences (Volgograd) and the Lower Volga Station for the selection of tree species (Kamyshin). Within the framework of the study, a scale was formed with a score grading of decorative features. The score-rating score for each species distributed the places in the ranking according to the set of decorative features: 1 place (206 points) - Pseudotsuga menziesii var. viridis (Schwer.) Franco, P. menziesii var. glauca (Mayr) Franco, 2nd place (192 points) - Juniperus vir-giniana L., 3rd place (188 points) - Platycladus orientalis (L.) Franco, 4th place (185 points) - J. sabina L., J. communis L., 5th place (183 points) - Thuja occidentalis L. Among a number of studied species, J. virginiana L., T. occidentalis L. are characterized by the greatest decorativeness and versatility of application., P. orientalis (L.) Franco, can be used to create group, single plantings, hedges, and high clipped walls.J. communis L., Pseudotsuga menziesii var. viridis (Schwer.) Franco, P. menziesii var. glauca (Mayr) Franco is more recommended for creating group compositional and single plantings. J. sabina L. for landscaping completely open dry and heavily lit slopes, creating green islands on the lawn.